Sexual Slavery: A Case Study of Joginis in South India. Issue 2 (December 2018) - Tejpal, Mansi
In the religious land of India, in the hearts of the bifurcated southern states of Telangana and Andhra Pradesh, there exists the exploitative custom of ritual sexual slavery—the Jogini system (a local variation of the Devadasi system) of marrying young girls to a deity. This social evil has resisted the legal measures aimed at curbing it until date, despite having been prohibited as per the Devadasi (Prohibition of Dedication) Act (the Jogini Act) which became a law in Andhra Pradesh in March 1988. Although education and increasing awareness of human rights have yielded great positive results in terms of the decline in initiations, yet cases indicating the existence of the system still exist. This article, based on a qualitative study of three Joginis (also addressed as Jogins ) in the Mahbubnagar district of Telangana, is an attempt to understand the reasons behind the persistent decline, yet existence, of this practice through the eyes of those directly affected by it—the Jogins, their families and the community.